Pengaruh Model Pembelajaran Kooperatif Tipe Cooperative Integratide Reading and Composition terhadap Perilaku Sosial dan Spiritual Siswa - Mardiah, Dedeh; Al-Hamdani, M.Djaswidi (Jurnal Penelitian Pendidikan Islam, 2017)
This quasi-experimental research article shows that the use of cooperative learning model (CIRC type) significantly improves social behavior and spiritual behavior; is much different than the use of conventional learning model. Teachers and students respond positively to the use of cooperative learning models of this type. Students feel happy and more active, more ready to work together.